PENGARUH LATIHAN DRILL SMASH TERHADAP KETEPATAN SMASH ATLET BULUTANGKIS PB. PERINTIS MUDA TRAYEMA - Yoga, Yoga Pratama; Muldan, Dadan; Budi, Budi (Journal of Physical Education and Sport Science, 2024)
Yoga Pratama (NIM. 172223097). Researcher's observations about the smash hits ofPB's male athletes. Young Trayeman pioneers in applying movements in playingbadminton are still lacking, so it is necessary to look for and explore the factorscausing it. The existence of these weaknesses, male athletes PB. Young PioneerTrayeman tries to improve himself in mastering basic techniques in the ability to playbadminton properly and correctly. Therefore, researchers are interested inconducting research on drill smash drills on smash accuracy in PB's male athletes.Trayeman Young Pioneers. This type of research is experimental research. Thedesign used in this study is "Control Groups Pretest-Posttest Design". From the tableof t-test results, it can be seen that the t-count is 6.364 and the t-table (df 10) is 2.228,while the significance value of p is 0.000. Because t arithmetic 6,364 t table 2,228and sig, 0,000 0,05, it means that there is a significant difference. Thus, it shows thatthe hypothesis (Ha) which reads "The experimental group with practice smash withthe drill smash method is better than the control group in increasing the accuracy ofsmash in PB badminton athletes. Trayeman Young Pioneers”, accepted. With apercentage increase of 30.93%. The experimental group with the drill smash methodwas better than the control group in increasing the accuracy of the PB badmintonathletes' smash. Trayeman Young Pioneers, with an average difference of 6.0.